Verbal Perceptual Prompts Facilitate Children’s Sensitivity to False Beliefs - Qiyu Huang; Xiuli Liu (Journal of Intelligence, 2024)
False belief understanding is always regarded as a milestone of Theory of Mind (ToM), which is an important aspect of social intelligence. Recently, some researchers have suggested the existence of two ToM systems in individuals: one that explicitly guides false belief understanding and another that implicitly directs sensitivity to false beliefs. However, studies on sensitivity to false beliefs have encountered challenges with replicability, and the factors influencing the manifestation of sensitivity to false beliefs remain to be explored. Based on the anticipatory looking task, we investigated whether verbal perceptual prompts could improve children’s performance of sensitivity to false beliefs. Fifty-eight children aged 5 to 6 were randomly assigned tasks with or without verbal perceptual prompts, involving verbal descriptions and explanations of the protagonist’s perceptual state. The findings showed that verbal perceptual prompts could slightly reduce children’s propensity to look at the actual location of the object in false belief situations and increase the likelihood of exhibiting accurate anticipatory looking patterns across false belief and true belief situations. The results suggest that children’s sensitivity to false beliefs may be situation-dependent, yet further investigation is needed to determine which situational factors can most effectively trigger robust sensitivity to false beliefs in children. The results enlighten educational practice, indicating that introducing cues in social environments that convey insights into others’ mental states, akin to the use of learning scaffolding, is advantageous for the development of children’s social cognitive abilities.